Agriculture Productivity and Environmental Degradation in Indonesia: A Time Series Analysis - Ariani, Rita; Fachrurrozi, Kamal; Adhiana, Adhiana; Baihaqi, Akhmad (International Journal of Energy Economics and Policy, 2024)
High carbon emissions pose a challenge in achieving sustainability. The agricultural sector is one of the contributors. This study aims to examine the relationship between the agricultural sector’s contribution, agricultural productivity, economic growth, fossil energy consumption, and carbon emissions in Indonesia. The research data covers the time period from 1990 to 2021. The analytical methods used include autoregressive distributed lag (ARDL) and cointegration testing with Bayer and Hanck. Additionally, causality testing is applied using the Toda-Yamamoto (TY) approach. The results indicate the existence of cointegration in all five models. Furthermore, the contributions of the agricultural sector, economic growth, and fossil energy consumption drive an increase in carbon emissions in both the short and long term. Meanwhile, agricultural productivity effectively reduces carbon emissions in both time horizons. Finally, each variable exhibits a two-way causal relationship.